2020
DOI: 10.24072/pci.evolbiol.100093
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis and the evolution of selfing

Abstract: The authors present a theoretical analysis of how epistasis can affect the evolution of selfing. By using a general model in which the contribution of different forms of epistasis to an individual's fitness can be analytically decomposed, the authors show not only that epistasis may increase the selective advantage of selfing, but also these forms may select for selfing in distinct ways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…We determined whether coevolution took place in our experiment by performing 13,500 timeshift assays. This approach assesses the infectivity of parasites toward their past, present, and future hosts and, reciprocally, the resistance of hosts to their past, present, and future parasites (21). Resistance was measured by inhibition assays in which individual host genotypes were challenged with parasite communities and resultant growth or inhibition was analyzed to compare the mean levels of resistance among treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We determined whether coevolution took place in our experiment by performing 13,500 timeshift assays. This approach assesses the infectivity of parasites toward their past, present, and future hosts and, reciprocally, the resistance of hosts to their past, present, and future parasites (21). Resistance was measured by inhibition assays in which individual host genotypes were challenged with parasite communities and resultant growth or inhibition was analyzed to compare the mean levels of resistance among treatments.…”
mentioning
confidence: 99%
“…We have previously shown that mutations in the LPS biosynthesis gene wzy provide resistance to four of the phages used in this study (14). Red Queen and arms race dynamics fall at two ends of a continuum (21): Tight interaction specificity is required for the former, and for the latter, general host resistance mechanisms should evolve to allow future hosts to resist all previous parasite genotypes. Our data point to the availability of generalist LPS biosynthesis Betts The genetic distances between coevolved populations were ordinated by nonmetric multidimensional scaling (MDS1 and MDS2).…”
mentioning
confidence: 99%